2017
DOI: 10.1002/adma.201606205
|View full text |Cite
|
Sign up to set email alerts
|

Highly Reproducible Organometallic Halide Perovskite Microdevices based on Top‐Down Lithography

Abstract: Highly reproducible organometallic-halide-perovskite-based devices are fabricated by a manufacturing process, which is demonstrated. Various shapes that are hard to synthesize directly are fabricated, and many unique properties are achieved.The fabrication procedure is utilized to create a photodetector and the detection sensitivity is significantly improved. The results will bring revolutionary advancement to the future of lead-halide-perovskite-based optoelectronic devices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
141
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 149 publications
(149 citation statements)
references
References 49 publications
8
141
0
Order By: Relevance
“…It is easy to see that the deviations in different samples are much smaller than 0.1 nm. This value is close to the spectral resolution of our spectrometer and even comparable to the variation in MAPbBr 3 microdisks that are fabricated with electron-beam lithography and reactive plasma etching, [26] clearly demonstrating the high reproducibility of MAPbBr 3 perovskite microdisks on the same wafer.…”
Section: Uniform Wgm Laser In Perovskite Microdiskssupporting
confidence: 80%
See 3 more Smart Citations
“…It is easy to see that the deviations in different samples are much smaller than 0.1 nm. This value is close to the spectral resolution of our spectrometer and even comparable to the variation in MAPbBr 3 microdisks that are fabricated with electron-beam lithography and reactive plasma etching, [26] clearly demonstrating the high reproducibility of MAPbBr 3 perovskite microdisks on the same wafer.…”
Section: Uniform Wgm Laser In Perovskite Microdiskssupporting
confidence: 80%
“…[22,23] With the developments of nanofabrication technologies, distributed feedback Bragg (DFB) laser and circular microdisk lasers with precise wavelength control and wellpreserved optical gain have been experimentally realized by either inductively coupled plasma etching or nanoimprinting. [24][25][26] Associated with the developments of isolated devices, lead halide perovskites devices arrays have attracted considerable research attention due to their potential applications in coherent light arrays, charge-coupled device (CCD) arrays, and integrated optoelectronic circuits. [27][28][29][30] Basically, the technologies for perovskite arrays can be categorized into two groups: those that split the stock solutions by patterning the substrate or by covering it with a periodic slide.…”
Section: Doi: 101002/lpor201700234mentioning
confidence: 99%
See 2 more Smart Citations
“…More specifically, a lithographic approach that can define desired perovskite patterns is highly needed in order to utilize these materials for the realization of integrated perovskite photonic devices. Zhang et al [25] demonstrated a different approach where PMMA layers were deposited on top of a MAPbBr 3 film and patterned using electron beam lithography (EBL) followed by dry Cl etching. First, the ability to cover the material (in our case perovskites) with a layer of resist and pattern it with sub-micrometer resolution using a scalable process.…”
mentioning
confidence: 99%